Relationship Between Sever Disease and Skeletal Maturity. Issue 2 (February 2020) - Duong, Mindy M.; Nicholson, Allen D.; Li, Samuel Q.; Gilmore, Allison; Cooperman, Daniel R.; Liu, Raymond W.
Abstract : Background: Sever disease is a common condition in active, growing children. This condition presents as pain in the heel and is thought to be an overuse condition of the calcaneal apophysis. There are currently no defined radiographic diagnostic criteria for evaluation of Sever disease, with radiographs generally showing normal appearance of the calcaneal apophysis. A better understanding of the relationship of Sever disease and skeletal maturity may allow for improved interpretation of radiographs when trying to diagnose this condition. Methods: ICD-9 code 732.5 was used to search for patients diagnosed with Sever disease from 2007 to 2015 at a single hospital. For every patient with Sever disease with available calcaneal imaging within 40 days of diagnosis, heel x-rays were staged for calcaneal maturity score using a previously described calcaneal skeletal maturity assessment system. Controls matched by age, race, and sex were evaluated for calcaneal stage to compare with the Sever patients. Results: The chart review yielded 78 patients diagnosed with Sever disease by the orthopaedic attending, 39 of which have x-rays around the time of diagnosis. Calcaneal scores averaged 2.2±0.8 for all patients, 2.1±0.9 for male individuals, and 2.3±0.8 for female individuals. The average age for male individuals was 10.4±1.9 years and for female individuals, 9.2±2.2 years. The ages of diagnosis were similar for patients with and without x-rays. Twenty-two of 39 patients with Sever disease were calcaneal stage 2, and 37 of 39 were stages 1, 2, or 3. We calculated the absolute difference from stage 2 for the Sever and control groups. Mean difference from stage 2 was 0.51±0.68 for the Sever patients and 0.95±0.79 for control patients ( P =0.01). Conclusion: Sever disease occurs in a very narrow range of skeletal maturity, as measured by the calcaneal skeletal maturity assessment system and our observations with chronological age. When compared with age-matched and race-matched controls, stage 2 was seen more frequently in the Sever patients. If a child is not within calcaneal stages 1, 2, or 3, then a different diagnosis should be considered. Level of Evidence: Level III—retrospective case-control study.